2020
DOI: 10.1177/0047287520951642
|View full text |Cite
|
Sign up to set email alerts
|

That’s Private! Understanding Travelers’ Privacy Concerns and Online Data Disclosure

Abstract: Against the backdrop of advancements in technology and its deployment by companies and governments to collect sensitive personal information, information privacy has become an issue of great interest for academics, practitioners, and the general public. The travel and tourism industry has been pioneering the collection and use of biometric data for identity verification. Yet, privacy research focusing on the travel context is scarce. This study developed a valid measurement of Travelers’ Online Privacy Concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 49 publications
1
24
0
1
Order By: Relevance
“…Such clusters differ in average perceived sensitivity but are often difficult to interpret in terms of semantic meaning. In contrast, factorization approaches revealed latent groups of personal data with increased interpretability [31,38,60]. In the field of employment, a study in 1973 [76] identified five factors of personal data from job interviews and found that questions about religious and ethnic, as well as financial backgrounds were perceived as inappropriate.…”
Section: Groups Of Personal Datamentioning
confidence: 99%
“…Such clusters differ in average perceived sensitivity but are often difficult to interpret in terms of semantic meaning. In contrast, factorization approaches revealed latent groups of personal data with increased interpretability [31,38,60]. In the field of employment, a study in 1973 [76] identified five factors of personal data from job interviews and found that questions about religious and ethnic, as well as financial backgrounds were perceived as inappropriate.…”
Section: Groups Of Personal Datamentioning
confidence: 99%
“…For example, when people doubt the value of a goal or feel uncertain about whether the goal can be achieved, they will feel a stronger epistemic need to reduce the ambiguity and become more likely to disclose their opinions and seek social validation from others (Eccles and Wigfield 2002). In the context of tourism consumption, tourism activities often involve a higher level of uncertainty than daily life (Su, Cheng, and Huang 2020;Ioannou, Tussyadiah, and Miller 2020). When tourists set a tourism goal, they are not sure if the upcoming trip will meet their expectations.…”
Section: Goal Disclosurementioning
confidence: 99%
“…Macroenvironmental factors, such as cross-cultural preferences, have been identified as antecedents of privacy concerns (Ioannou et al, 2020;Tussyadiah et al, 2019). Research on privacy has shown that culture impacts consumers' attitudes toward privacy concerns (Bellman et al, 2004;Cullen, 2009;Dinev et al, 2006;Milberg et al, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through which lenses can privacy concerns be scrutinized in tourism and hospitality? Recent studies have acknowledged the scarcity of investigations into hotel guests' physical privacy concerns and have, thus called for more research to assess this relevant aspect of guests' experiences (Hall and Ram, 2019;Ioannou et al, 2020;Tussyadiah et al, 2019). In this vein, the present study sought to explore the privacy concerns of hotel guests and their evolution over time.…”
Section: Introductionmentioning
confidence: 99%